Efficient Treatment of Sporothrix globosa Infection Using the Antibody Elicited by Recombinant Phage Nanofibers - Chen, Feng; Jiang, Rihua; Dong, Shuai; Yan, Bailing (Frontiers in Pharmacology, 2019)
Antifungal therapy is used to treat sporotrichosis. However, there are several limitations in this therapy, such as development of drug resistance and potential health risks including liver injury. The purpose of our study was to evaluate the antifungal efficacy of antibody against the hybrid phage nanofibers displaying KPVQHALLTPLGLDR (phage-KR) in a fungal-infected mouse model. In this study, we extracte an antibody against hybrid phage nanofibers (phage-KR) from immunized mice and passively inoculate Sporothrix globosa (S. globosa) infected mice. The study shows that the antibody exhibits efficient inhibition efficacy of the S. globosa infection, including reduction of the progressive fungi colonizing, increase of animal survival rate and relief of organ inflammation in the mice. The results indicate that antibody against phage-KR may act as a potential strategy for safe and efficient treatment of S. globosa infections.